A Convenient Microwave‐Assisted Propylphosphonic Anhydride (T3P®) Mediated One‐Pot Pyrazolone Synthesis. Issue 26 (29th July 2013) - Desroses, Matthieu; Jacques‐Cordonnier, Marie‐Caroline; Llona‐Minguez, Sabin; Jacques, Sylvain; Koolmeister, Tobias; Helleday, Thomas; Scobie, Martin
Abstract: This paper describes a facile, efficient, and clean synthesis of various pyrazolones by employing T3P ® as a catalyst and performing the reaction under microwave irradiation. This two‐step, one‐pot reaction proceeded readily and tolerated a variety of functional groups. A wide range of pyrazolone derivatives were obtained in good to excellent yields. Abstract : A one‐pot, two‐step procedure for the synthesis of pyrazolones is presented. This method, which uses T3P ® and microwave irradiation, is particularly easy to carry out and offers a notable alternative to the strongly acidic conditions that are generally employed with other synthetic approaches.